Human Kinetoplastid Protozoan Infections: Where Are We Going Next? - Filardy, Alessandra Almeida; Guimarães-Pinto, Kamila; Nunes, Marise Pinheiro; Zukeram, Ketiuce; Fliess, Lara; Pereira, Ludimila; Oliveira Nascimento, Danielle; Conde, Luciana; Morrot, Alexandre (Frontiers in Immunology, 2018)
Kinetoplastida trypanosomatidae microorganisms are protozoan parasites exhibiting a developmental stage in the gut of insect vectors and tissues of vertebrate hosts. During the vertebrate infective stages, these parasites alter the differential expression of virulence genes, modifying their biological and antigenic properties in order to subvert the host protective immune responses and establish a persistent infection. One of the hallmarks of kinetoplastid parasites is their evasion mechanisms from host immunity, leading the disease chronification. The diseases caused by kinetoplastid parasites are neglected by the global expenditures in research and development, affecting millions of individuals in the low and middle-income countries located mainly in the tropical and subtropical regions. However, investments made by public and private initiatives have over the last decade leveraged important lines of intervention that if well-integrated to health care programs will likely accelerate disease control initiatives. This review summarizes recent advances in public health care principles, including new drug discoveries and their rational use with chemotherapeutic vaccines, and the implementation of control efforts to spatially mapping the kinetoplastid infections through monitoring of infected individuals in epidemic areas. These approaches should bring us the means to track genetic variation of parasites and drug resistance, integrating these data with effective stewardship programs to prevent vector-borne kinetoplastid infections in areas at risk of disease spreading.